2020
DOI: 10.3126/kumj.v18i2.32943
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning in the Face of COVID-19 Pandemic: Assessment of Students’ Satisfaction at Chitwan Medical College of Nepal

Abstract: Background Online learning can play a vital role in the process of teaching and learning during Corona Virus Disease 2019 (COVID-19) pandemic. However, learners’ satisfaction is extremely important in effective implementation of the online learning, especially at institutions where it is newly adopted. Objective To assess satisfaction towards online learning and its predictors among students at Chitwan Medical College, Bharatpur. Method A web-based cross-sectional survey was undertaken among 434 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
85
8
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 23 publications
11
85
8
21
Order By: Relevance
“…Both the online anatomy lectures and pre-recorded lectures left 56.0% and 52.5% of students satisfied. These findings, are similar to the 53.5% reported in Sharma et al [11] study and close to the 63.4% in Cuschieri and Agius [12] cohort. However, in the relevant literature there are studies mentioning more than 87% satisfaction [7,13], contrariwise to others reporting lower than 14% satisfaction [8,14] with the online educational methods in health sciences (medicine, dentistry, pharmacy etc.).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both the online anatomy lectures and pre-recorded lectures left 56.0% and 52.5% of students satisfied. These findings, are similar to the 53.5% reported in Sharma et al [11] study and close to the 63.4% in Cuschieri and Agius [12] cohort. However, in the relevant literature there are studies mentioning more than 87% satisfaction [7,13], contrariwise to others reporting lower than 14% satisfaction [8,14] with the online educational methods in health sciences (medicine, dentistry, pharmacy etc.).…”
Section: Discussionsupporting
confidence: 92%
“…However, 34.5% of the students would like some of the lectures to become remotely. In studies coming from Nepalese, Pakistani and Kuwait students, it was highlighted that 89.8%, 77% and 51.2% of these students respectively, prefer to continue the online lectures [11,21,22]. This inconsistency may reflect different perspectives between Nations and disparities in the traditional and /or the online learning modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike this finding, a study conducted by Abuhassna et al (2020) has reported that students had highly satisfied with online teaching. To consider the overall level of satisfaction with online teaching, several studies have been found in line with the findings of the present study (Aristovnik et al, 2020;Babinčáková & Bernard, 2020;Bauk et al, 2014;Bokayev et al, 2021;Bolliger & Wasilik, 2009;Chen et al, 2020;Durak, 2020;Fatani, 2020 2020; Mahdy, 2020bMahdy, , 2020aMalkawi et al, 2021;Nguyen, 2016;Di Pietro et al, 2020;Shahzadi & Ahmad, 2011;Sharma et al, 2020;Surahman & Sulthoni, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The findings of a study revealed by Baber (2020) are in line with the indicated studies where the researcher found a positively great level of satisfaction in providing online teaching. In contrast, the findings of the study revealed by Sharma et al (2020) indicated that the majority of their respondents are dissatisfied with online learning platforms. Similarly, the findings of a study revealed by Dinh and Nguyen (2020) show that online teaching and learning had a lower satisfaction level than face-to-face teaching.…”
Section: Review Of Related Workmentioning
confidence: 70%
See 1 more Smart Citation